2010
DOI: 10.1021/ma902797f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Heterogeneity in PNA:PNA Duplexes

Abstract: Oligomers of PNA:PNA duplexes with different amino acids appended to one strand of each duplex have been synthesized and studied for their chiral optical properties. The terminal amino acid is known to affect both the handedness and amplitude of the CD signal from a given duplex. Here we have investigated an extended set of duplexes with several different amino acids appended, determining the CD, absorbance, and denaturation behavior of these chains in water and glycerol. Thermal unfolding profiles of the dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 61 publications
5
33
0
Order By: Relevance
“…The phenomena discussed above will pertain to varieties of systems, consistent with the several examples given above, but within the restriction that chiral information input does not act as a structural modifier 19. There are many more examples in the literature where these general ideas have found value and a proper review of the subject, rather than an overview of the principles as intended here, may be of interest.…”
Section: Discussionmentioning
confidence: 68%
“…The phenomena discussed above will pertain to varieties of systems, consistent with the several examples given above, but within the restriction that chiral information input does not act as a structural modifier 19. There are many more examples in the literature where these general ideas have found value and a proper review of the subject, rather than an overview of the principles as intended here, may be of interest.…”
Section: Discussionmentioning
confidence: 68%
“…It has been shown by some of us that PNA containing three intrinsically chiral monomers, bearing either a D‐ or L‐lysine side chain at the C2–(α) carbon atom, form parallel PNA:PNA duplexes with achiral complementary PNA of handedness opposite to that of the corresponding antiparallel duplexes . Later on, we studied the propagation of the helicity generated by a terminal chiral amino acid in antiparallel PNA:PNA duplexes . In order to better understand the structural features of PNA parallel duplexes and the induction of chirality in these systems by a terminal chiral amino acid, we explored the possibility to use porphyrins covalently linked to the N‐terminus of PNA ( P1P and P2P ) as a CD reporter of supramolecular chirality upon duplex formation (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, these artificial DNA mimics have also found attractive applications in nanotechnology as programmable helical structures with different helical pitch and increased stability towards chemical and enzymatic degradation, as tools in molecular computing, and as new self‐assembled materials for optical and optoelectronic applications . One of the key features of PNA is the possibility to form homo‐duplexes, where the helix handedness can be controlled by insertion of suitable chiral centers, so that either right‐ or left‐handed helices can be obtained . While the structural features of antiparallel PNA duplexes (formed by two strands with opposite N‐terminus → C‐terminus orientation) have been extensively studied, parallel PNA:PNA duplexes are still not fully characterized .…”
Section: Methodsmentioning
confidence: 99%
“…Gupta et al Journal of Biotechnology 259 (2017) 148-159 therapeutics. Totsingan and group (Totsingan et al, 2010) synthesized and studied the chiral optical properties of different oligomers of PNA/ PNA duplexes, where different amino acids were attached at the terminal of a single strand of each duplex. In this statistical theoretical model, it was observed that the PNA/PNA double helix had access to a dynamic ensemble of conformational states in solution which varied as a function of oligomer length.…”
Section: Pna/pna Duplexesmentioning
confidence: 99%